PENERAPAN PEMBELAJARAN BERDIFERENSIASI TERHADAP KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK - Nuraini; Alfiandra (STKIP Subang, 2024)
This study aims to describe the Application of Differentiated Learning to Students' Creative Thinking Abilities. The research method used in this study is descriptive with a literature study approach. The results of this study indicate that the application of differentiated learning is a new paradigm carried out through the educational process in improving students' creative thinking abilities. Differentiated learning is a new approach in the Independent Curriculum and one of the steps in implementing the character profile of Pancasila students, especially creative characters. Creative thinking skills are abilities that must be possessed by students in responding to the challenges of 21st century learning which is developing rapidly. The process of implementing differentiated learning through four aspects, namely differentiated contests, differentiated processes, differentiated products, and differentiated learning environments has a significant influence on students' creative thinking abilities.